First observation of CP violation in the decays of B0s mesons - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physical review letters, 2013)
Using pp collision data corresponding to an integrated luminosity of 1.0 fb−1 and collected by LHCb in 2011 at a center-of-mass energy of 7 TeV, we report the measurement of direct CP violation in B0s→K−π+ decays, ACP(B0s→K−π+)=0.27±0.04 (stat)±0.01 (syst), with significance exceeding 5 standard deviations. This is the first observation of CP violation in the decays of B0s mesons. Furthermore, we provide an improved determination of direct CP violation in B0→K+π− decays, ACP(B0→K+π−)=−0.080±0.007 (stat)±0.003 (syst), which is the most precise measurement of this quantity to date.